A murder in Virginia: southern justice on trial - Lebsock, Suzanne (Norton, 2003)
Murder most brutal -- Chase City -- Flight -- Independence Day -- Solomon on trial -- Quick work -- The prince of liars -- Mirabile Marable -- The rise of Edward Pollard -- The thirteenth juror -- Taking sides -- Baptisms -- White-man stories -- Nunc pro tunc -- New life -- A gone case -- Egg-sucking dog -- Tracks -- One shall be taken -- Messages -- Solomon's body -- Common sense -- The pitcher to the well -- Who killed Lucy Pollard?